Added Value of Estrogen Receptor, Progesterone Receptor, and L1 Cell Adhesion Molecule Expression to Histology-Based Endometrial Carcinoma Recurrence Prediction Models: An ENITEC Collaboration Study. Issue 3 (March 2018) - van der Putten, Louis J.M.; Visser, Nicole C.M.; van de Vijver, Koen; Santacana, Maria; Bronsert, Peter; Bulten, Johan; Hirschfeld, Marc; Colas, Eva; Gil-Moreno, Antonio; Garcia, Angel; Mancebo, Gemma; Alameda, Fransesc; et al.
Abstract : Objectives: Endometrial carcinoma mortality is mainly caused by recurrent disease, and various immunohistochemical markers to predict recurrences have been studied. Loss of the estrogen receptor (ER) and progesterone receptor (PR) and the presence of the L1 cell adhesion molecule (L1CAM) are promising markers, but their combined value has not been studied. Materials and Methods: Expression of ER, PR, and L1CAM was immunohistochemically determined in 293 endometrial carcinomas from 11 collaborating European Network for Individualized Treatment of Endometrial Cancer centers. Estrogen receptor, PR, or L1CAM staining was considered positive or negative when expressed by greater than or equal to 10% or less than 10% of the tumor cells, respectively. The association between these markers and clinicopathological markers, and their combined value in predicting survival were calculated, both in the entire cohort and in a selected groups of stage I endometrioid and low-risk stage I endometrioid carcinomas. Results: Estrogen receptor and PR were negative in 19% and 28% of the cases, respectively, and L1CAM was positive in 18%. All 3 were associated with advanced stage, high-grade, nonendometrioid histology, lymphovascular space invasion (LVSI), and reduced disease-free survival. Only advanced stage, loss of PR, and LVSI were associated with reduced disease-free survival in multivariate analysis. A prognostic model including these 3 markers was superior to 1 including only the 3 immunohistochemical markers, which was superior to the traditional model. In both the stage I endometrioid and the low-risk stage I endometrioid groups, only loss of PR was associated with reduced disease-free survival. Conclusions: Loss of ER and PR, and the presence of L1CAM are associated with high risk characteristics, and loss of PR is the strongest predictor of recurrent disease. Although a combination of these 3 markers is slightly superior to the traditional histological markers, a prognostic model including stage, PR expression, and LVSI is the most promising model in the identification of high risk carcinomas. In the stage I endometrioid carcinomas, PR immunohistochemistry appears to be of additional value in predicting recurrences.